Receptor for Advanced Glycation End Products: Dementia and Cognitive Impairment - Singh, Aditya; Ansari, Vaseem Ahamad; Mahmood, Tarique; Ahsan, Farogh; Wasim, Rufaida; Shariq, Mohammad; Parveen, Saba; Maheshwari, Shubhrat (Drug Research, 2023)
The pathophysiological processes of dementia and cognitive impairment are linked to advanced glycation end products (AGEs) and their receptor (RAGE).The neurofibrillary tangles (NFTs) of abnormally hyperphosphorylated tau protein and senile plaques (SPs), which are brought on by amyloid beta (Aβ) deposition, are the hallmarks of Alzheimer’s disease (AD), a progressive neurodegenerative condition. Advanced glycation end products that are produced as a result of vascular dysfunction are bound by the receptor for advanced glycation end products (RAGE). Dementia and cognitive impairment could develop when RAGE binds to Aβ and produces reactive oxygen species, aggravating Aβ buildup and ultimately resulting in SPs and NFTs. RAGE could be a more powerful biomarker than Aβ because it is implicated in early AD. The resident immune cells in the brain known as microglia are essential for healthy brain function. Microglia is prominent in the amyloid plaques’ outside border as well as their central region in Alzheimer’s disease. Microglial cells, in the opinion of some authors, actively contribute to the formation of amyloid plaques. In this review, we first discuss the early diagnosis of dementia and cognitive impairment, and then detail the interaction between RAGE and Aβ and Tau that is necessary to cause dementia and cognitive impairment pathology, and it is anticipated that the creation of RAGE probes will help in the diagnosis and treatment of dementia and cognitive impairment.
Keywords: AGE; dementia; cognitive impairment; aβ; tau; senile plaques